Clinical and Magnetic Resonance Imaging Predictors of Very Early Neurological Response to Intravenous Thrombolysis in Patients With Middle Cerebral Artery Occlusion. Issue 6 (5th December 2013) - Apoil, Marion; Turc, Guillaume; Tisserand, Marie; Calvet, David; Naggara, Olivier; Domigo, Valérie; Baron, Jean‐Claude; Oppenheim, Catherine; Touzé, Emmanuel
Abstract : Background: The early identification of patients who are unlikely to respond to intravenous recombinant tissue plasminogen activator (IV‐tPA) could help select candidates for additional intra‐arterial therapy or add‐on antithrombotic drugs during the acute stage of stroke. Given that very early neurological improvement (VENI) is a reliable surrogate of early recanalization, we assessed the clinical and magnetic resonance imaging predictors of lack of VENI. Methods and Results: We reviewed consecutive ischemic stroke patients with middle cerebral artery occlusion and treated within 4.5 hours by IV‐tPA between 2003 and 2012 in our center, where magnetic resonance imaging is systematically implemented as first‐line diagnostic workup. Lack of VENI was defined as a <40% decrease in baseline National Institutes of Health Stroke Scale (NIHSS) score 1 hour after start of IV‐tPA. Poor outcome was defined as a 3‐month modified Rankin scale ≥2. Associations between lack of VENI and potential determinants were assessed in logistic regression models. In all, 186 patients were included (median baseline NIHSS score, 16; median onset to treatment time, 155 minutes). One hundred forty‐three patients (77%) had no VENI. The variables significantly associated with lack of VENI in multivariable analysis were baseline NIHSS (OR, 1.08; 95% CI, 1.01 to 1.16 per 1‐point increase; P =0.03), onset to treatment time >120 minutes (OR, 2.94; 95% CI, 1.31 to 6.63; P =0.009) and diffusion weighted imaging—Alberta Stroke Programme Early CT Score ≤5 (OR, 3.60; 95% CI, 1.14 to 11.35; P =0.03). Patients without VENI were more likely to have a modified Rankin Scale ≥2 than those without VENI (68% versus 24%; OR, 5.01; 95% CI, 2.12 to 11.82) and less likely to have recanalization after 24 hours (OR, 0.41; 95% CI, 0.19 to 0.88). Conclusions: Lack of VENI provides an early estimate of 3‐month outcome and recanalization after IV‐tPA. Baseline NIHSS, onset to treatment time, and diffusion weighted imaging—Alberta Stroke Programme Early CT Score could help to predict lack of VENI and, in turn, might help early selection of candidates for complementary reperfusion strategies.